Perception and Attitude of Educators towards Students with Disabilities: A Narrative Literature Review - Kabe, P. J.; Mulaudzi, V.; Rantho, K. M. (Technium Social Sciences Journal, 2021)
People living with disability are seen as the population vulnerable to various social ills, in academic it is not an exception. In most instance, people living with disability receive negative attitude from their educator and thus derail their progress. As such, this paper was aimed at highlighting the perceptions and attitude of educators towards students with disability. The researchers used a narrative literature review as a research design in order to provide the synthesis evidence on the perceptions and attitude of educators towards students with disability. In order to have a user friendly information, the researcher had to limit their search and use documents that are peer reviewed. On that score, the researcher used purposive sampling techniques in order to select peer reviewed published articles from 2008 to 2020 from different platforms such as Google Scholar, Ebscohost, Jastor and ScienceDirect. As part of the inclusion-exclusion criteria, the researchers carefully selected articles which were within the delimited number of years and excluded those documents which were not peer reviewed and fall out of the selected years. Then the data were analysed thematically. The study found that educators have limited information of how to deal with students living with disabilities.